Structural Features Required for Inhibition of Soybean Lipoxygenase-2 by Propyl Gallate : Evidence that Lipoxygenase Activity Is Distinct from the Alternative Pathway - Peterman, T. Kaye (1983)
The ability of 19 structural analogs of propyl gallate to inhibit purified soybean seed (Glycine max [L.] Merr. var. Ransom) lipoxygenase-2 (EC 1.13.11.12) was determined. The results indicate that the o-dihydroxy and not the ester function of propyl gallate is essential for inhibition of lipoxygenase. Catechol thus represents the minimum inhibitory structure. Among those compounds possessing an o-dihydroxy function, the K(i)′ for inhibition of lipoxygenase is directly related to the lipophilicity of the inhibitor as measured by the octanol-water partition coefficient. The structural features of propyl gallate necessary for inhibition of lipoxygenase were found to differ from those required for inhibition of the plant mitochondrial alternative pathway. This further supports the concept that the alternative oxidase and lipoxygenase are functionally distinct species.